The effect of four-phase teaching method on midwifery students’ emotional intelligence in managing the childbirth - Mohamadirizi, Soheila (J Educ Health Promot, 2015)
BACKGROUND: An active teaching method has been used widely in medical education. The aim of this study was to determine the effectiveness of the four-phase teaching method on midwifery students’ emotional intelligence (EQ) in managing the childbirth. MATERIALS AND METHODS: This was an experimental study that performed in 2013 in Isfahan University of Medical Sciences. Thirty midwifery students were involved in this study and selected through a random sampling method. The EQ questionnaire (43Q) was completed by both the groups, before and after the education. The collected data were analyzed using SPSS 14, the independent t-test, and the paired t-test. The statistically significant level was considered to be <0.05. RESULTS: The findings of the independent t-test did not show any significant difference between EQ scores of the experimental and the control group before the intervention, whereas a statistically significant difference was observed after the intervention between the scores of two groups (P = 0.009). The paired t-test showed a statistically significant difference in EQ scores in the two groups after the intervention in the four-phase and the control group, respectively, as P = 0.005 and P = 0.018. Furthermore, the rate of self-efficiency has increased in the experimental group and control group as 66% and 13% (P = 0.024), respectively. CONCLUSION: The four-phase teaching method can increase the EQ levels of midwifery students. Therefore, the conduction of this educational model is recommended as an effective learning method.